2019
DOI: 10.1007/s13361-019-02235-1
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenated Gold Clusters from Helium Nanodroplets: Cluster Ionization and Affinities for Protons and Hydrogen Molecules

Abstract: We report the mass spectrometric detection of hydrogenated gold clusters ionized by electron transfer and proton transfer. The cations appear after the pickup of hydrogen molecules and gold atoms by helium nanodroplets (HNDs) near zero K and subsequent exposure to electron impact. We focus on the size distributions of the gold cluster cations and their hydrogen content, the electron energy dependence of the ion yield, patterns of hydrogenated gold cluster cation stability, and the presence of “magic” clusters.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…The experiments utilize the ultracold environment of helium nanodroplets (HND) as a nano matrix for the formation of cold, mixed complexes with gold as described in [10][11][12][13][14]16,51,63]. The experimental setup which is schematically shown in Figure 9 has been described previously in [64].…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiments utilize the ultracold environment of helium nanodroplets (HND) as a nano matrix for the formation of cold, mixed complexes with gold as described in [10][11][12][13][14]16,51,63]. The experimental setup which is schematically shown in Figure 9 has been described previously in [64].…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The presence of a gold atom in the cluster ions strongly enhances (factor 16.4) stoichiometric ions. Lundberg et al recently investigated hydrogenated gold cluster ions and observed a markedly different trend of the hydrogen attachment to odd and even numbered gold clusters [51]. According to quantum chemical calculations at the MP2/def2-TZVP level of theory, a hydrogen atom appears to bridge two Au atoms in hydrogenated cluster ions with an even number of Au atoms.…”
Section: Ligandmentioning
confidence: 99%
“…With the invention of superfluid helium droplets, a new method of cluster formation has been discovered; the high pickup efficiency of large superfluid helium droplets is ideal for forming molecular and atomic clusters. 32–38 For volatile species, the doping pressure can be controlled by the temperature or the opening time of a sample-containing pulse valve (SPV). For non-volatile species including refractive metals, heating ovens have been used to supply the sample molecules or atoms.…”
Section: Superfluid Helium Droplets and Formation Of Clustersmentioning
confidence: 99%
“…In the lower m/z region, only Au m + ( m = 1–5) and Au m Fe + ( m = 1–5) clusters were identified, and, in the whole m / z region, Au m Fe + clusters up to m = 35 were observed. Mass spectra for the m/z range 1100–2900 are shown in Figure 3 with dominant signals of clusters that contain an odd number of gold atoms (odd‐even alternation) . In addition, the formation of gold‐carbide clusters was observed, which are shown in Figure 3 with the symbol “*”, and also Au m C 2 H + ( m = 6, 8, 10, 11, and 13), Au m C 2 H 2 + ( m = 6 and 8), Au 8 C 3 H + , Au 8 C 3 H 2 + , Au 8 C 4 H + , and Au 8 C 4 H 2 + .…”
Section: Resultsmentioning
confidence: 99%